Optical, structural, surface topographical and DFT studies of lead telluride (PbTe) thin film for photovoltaic applications - Cardenas-Jiron, G (Elsevier Ltd, 2026)
In this study, cubic-phase lead telluride (PbTe) thin films with 200, 400, and 600 nm thickness are fabricated by physical vapour-deposition method under inert gas atmospheric conditions. PbTe thin film has high crystallinity with cubic phase, micro and nanostructure growth on the glass substrates. The observation of 400 nm-thick PbTe thin films with reduced surface roughness (Ra) provides direct evidence from contact angle measurements. Results suggest that PbTe thin film with a 400 nm thickness layer is a suitable and stable absorber layer for photovoltaic applications. A series of periodic slab models containing two to seven atomic layers was constructed from the optimized bulk structure of cubic-phase PbTe, and the electronic properties were calculated using density functional theory (DFT). Band structure and projected density of states calculations show Te dominates the valence bands, and Pb 3p orbitals determine the conduction bands, with a larger band gap energy for even-layer systems than odd-layer systems. This could be attributed to a greater structural symmetry, which favors higher degeneracy of states in the former. These results indicate better agreement between even-layer systems and experimental data. A significant difference in the optical properties is found, showing a higher absorption in the visible region for the even-layer systems, which could be understood as a quantum confinement that increases the density of electronic states available for optical transitions. The experimental and theoretical results highlight the importance of thickness control in designing optoelectronic devices based on 2D materials. © 2025